Who's in the Jungle - Graves Sue (China : Parragon, 2003)
Who's in the Jungle?" is a children's book that introduces young readers to various jungle animals through interactive elements. The book provides clues about different jungle creatures, encouraging children to guess the animal before revealing the answer by lifting flaps or turning pages. This interactive approach engages children and aids in developing their cognitive and motor skills. The book features vibrant illustrations and simple text, making it suitable for early readers. It is available in various formats, including board books, ensuring durability for young hands